Sonoridade da floresta: grupo raízes caboclas - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The present research discusses the sonority of the Raízes Caboclas Group since 1982 to 2007 and its formation and musical development in the course of these years, since its begin in Benjamin Constant and its change to Manaus in 1989 In search of visibility and space in the artistic environment This investigation envolves three moments: the beginning of the Raizes Caboclas and its poetic-musical proposal; The analysis of the songs and its themes and the sale of discs and the acceptance of the Raízes Caboclas proposal by the public and the amazonian media. This study tries to understand the sonority produced by the musicians in singing the rivers, the forests, the legends and the myths of the region, emphasizing the valorization of the man from Amazon hinterlands (the caboclo) and the indigenous peoples, to point the idea of preservation in its letters. The use of bioinstruments, the constant search of sounds offered by the forest in its compositions and the original performances in concerts complete the sound research that we intend to develop.
Keywords: Sonoridade; Caboclo; Amazônia; Cultura; Sonority; Society; Culture; CIENCIAS HUMANAS